Institutions and institutional logics in construction safety management: the case of climatic heat stress. Issue 6 (3rd June 2017) - Jia, Andrea Yunyan; Rowlinson, Steve; Loosemore, Martin; Xu, Mengnan; Li, Baizhan; Gibb, Alistair
Abstract: We employed a Glaserian grounded theory approach to explore the gap between behavioural safety and its unsatisfactory outcomes. Data were collected through ethnographic studies on the practice of managing heat stress on thirty-six construction sites in Hong Kong and Chonqing in mainland China. Two core concepts, institutions and institutional logics, are generated and defined to explain why safety rules do not necessarily produce safety behaviours. At society level, we explicated two pairs of institutional logics: the religion logics (Confucianism vs. pragmatism) and the market logics (rational market vs. individualism). At project organizational level, two logics of processing safety in production are explicated: a protection logic in the Chongqing context and a production logic in the Hong Kong context. The concepts and sub-concepts are compared to existing business literature for clarification of scopes. Empirical findings of the study suggest safety intervention needs to redirect its focus from promoting safety alone to addressing the institutional logics of the entire organization and its societal context practised by multiple levels of actors. We conclude that safety research would benefit from redirecting its focus of analysis from discourses, interviews or surveys to authenticated cases reconstructed through triangulation of actors' discourses at multiple levels of an organization, third-party observation, physiological data and objective measurement of the work environment. Methodologically, this paper provides a detailed guidance for conducting grounded theory research with a focus of conceptualization.